2020
DOI: 10.11591/ijere.v9i2.20339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment big data in Nigeria: Identification, generation and processing in the opinion of the experts

Abstract: As a result of increasing complexity of assessing all aspects of human behaviours, a lot of data are generated on individual learner and from teachers and the system. What qualifies as big data in assessment in Nigeria? This research identifies the sources of assessment big data in Nigeria, investigates how the big data are generated and processed, and identifies the problems of generating and processing assessment big data in Nigeria. Through purposive sampling technique forty-five experts in education assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This is closely followed by lack of in-house data scientists and the high cost of engaging experienced ones (mean = 4.51), data security challenges (mean = 4.49) and the fact that big data takes a substantial investment of time, effort, and resources for proper maintenance (mean = 4.07). This confirms the findings of previous studies (Cope & Kalantzis, 2016;Esomonu et al, 2020;Macfadyen et al, 2014) that showed that security issues, low level of infrastructural development and technical know-how and lack of trained ICT officers among others are the major problems of utilizing big data.…”
Section: Hindrances To the Adoption Of Big Data In Property Marketingsupporting
confidence: 91%
“…This is closely followed by lack of in-house data scientists and the high cost of engaging experienced ones (mean = 4.51), data security challenges (mean = 4.49) and the fact that big data takes a substantial investment of time, effort, and resources for proper maintenance (mean = 4.07). This confirms the findings of previous studies (Cope & Kalantzis, 2016;Esomonu et al, 2020;Macfadyen et al, 2014) that showed that security issues, low level of infrastructural development and technical know-how and lack of trained ICT officers among others are the major problems of utilizing big data.…”
Section: Hindrances To the Adoption Of Big Data In Property Marketingsupporting
confidence: 91%
“…There more effective approaches during assessment process of virtual learning could be considered as follows: True-False (TF), Short Answer and Multiple-choice format. Some previous studies investigated the comparability of assessment determination and approaches (Esomonu et al, 2020). The usual used format in e-assessment is consisted of true-false.…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation activity is generally carried out conventionally (Barua, Singh, Mridiula, Gupta, Satyapriya & Tomar, 2017;Hardianti,Taufiq & Pamelasari, 2017;Abdurrahman, Saregar & Umam, 2018;Ozan, 2019;Violato & King, 2021). However, with the development of technology, evaluation can be integrated with technology (Sakar, Orhan, Sinanoğlu, Tosun & Öz, 2017;Ayanwale, Isaac-Oloniyo & Abayomi, 2020;Esomonu, Esomonu & Eleje, 2020). So it is necessary to develop a technology-based assessment system to facilitate the assessment process.…”
Section: Introductionmentioning
confidence: 99%